2009
DOI: 10.1002/mas.20241
|View full text |Cite
|
Sign up to set email alerts
|

ICP‐MS‐Based strategies for protein quantification

Abstract: In the post-genomics era, proteomics has become a central branch in life sciences. An understanding of biological functions will not only rely on protein identification, but also on protein quantification in a living organism. Most of the existing methods for quantitative proteomics are based on isotope labeling combined with molecular mass spectrometry. Recently, a remarkable progress that utilizes inductively coupled plasma-mass spectrometry (ICP-MS) as an attractive complement to electrospray MS and MALDI M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(92 citation statements)
references
References 146 publications
0
92
0
Order By: Relevance
“…Inductively coupled plasma-mass spectrometry (ICP-MS; Wang et al, 2009) was conducted to determine metal ligand composition for the recombinant RfLacA protein. Prior to digestion, protein samples were dialyzed to remove unbound metals.…”
Section: Inductively Coupled Plasma-mass Spectrometry Analysis Of Boumentioning
confidence: 99%
“…Inductively coupled plasma-mass spectrometry (ICP-MS; Wang et al, 2009) was conducted to determine metal ligand composition for the recombinant RfLacA protein. Prior to digestion, protein samples were dialyzed to remove unbound metals.…”
Section: Inductively Coupled Plasma-mass Spectrometry Analysis Of Boumentioning
confidence: 99%
“…Not only metal-containing biomolecules, but also other biomolecules, such as amino acids, peptides, proteins, nucleic acids and microbial cells, can be successfully quantified by measuring heteroatoms, such as phosphorus and sulfur, and/or by supporting elemental tags, such as metal-labeled antigens and nanoparticles. [4][5][6][7][8][9][10] In recent years, cytometric analysis of single cells with a time-resolved ICP-MS measurement is receiving much attention for elemental [14][15][16][17][18] and multiparametric [19][20][21][22][23] analyses of single cells. Due to cellular heterogeneity within an isogenic cell population, individual analysis of cells will lead to a more sensitive representation of cell-to-cell variations, instead of a stochastic average analysis by bulk measurements.…”
Section: Special Reviewsmentioning
confidence: 99%
“…However, CYP2E1 levels appear to be modulated to some extent by the compounds So far, the previous applications have been related to the labelling of antibodies used for immune-reactions, but in the following example it should be demonstrated that this procedure can also be applied for proteins directly, as it was discussed in a review article recently. 370 Ahrends et al 371,372 used metal-coded affinity tags (MeCAT) for direct labelling of standard proteins and eye lens proteins for quantitative ICP-SFMS. As MeCAT reagents they chose derivatives of the lanthanide chelating DOTA to which a cysteine reactive maleimide moiety was attached via a spacer.…”
Section: Speciation Analysismentioning
confidence: 99%